Roles Mapping in Tribal Conflict Reconciliation: A Study of West Kalimantan Dayak and Madurese Case - Ira Mirawati (MediaTor)
The Tribal conflict between Dayak and Madurese of West Kalimantan in 1996 – 2000 causing their communication had totally broken for many years. In 2002, they began to communicate. Until now, they still improve their communication quality. It is important to know how they conduct this reconciliation communication after all of their conflict. This research investigates people roles in the reconciliation communication between Dayak and Madurese in Kabupaten Bengkayang, West Kalimantan. Researcher using in-depth interview, observation, and literature study in this Phenomenology research. Nineteen informants were chosen purposively. They are both Dayak and Madurese, people from other tribe, police, and government officer. The result shows there are four roles in this communication; they are Dayaknese and Madurese as the main actor or performer, the guarantor as a mediator, the police officer and local government officer as an advisor, and other ethnics as colleagues. Madurese needs guarantor to ensure their live. Dayak and Madurese need an advisor when they facing a problem. Both of them also need other ethnics as colleagues to smooth communication. All of them played a role dramaturgically in positive purposes, as a personal or as a team member.